Application Program In Visual Basic 6.0 The learning process of work and energy - SIREGAR (NIM 20207072), HOIRUN
Discussion of moving object at inclined plane is more interested and more understood by animation. Animation can be created using the program Visual Basic 6.0. Using this program, students can easily understand about work and energy. In this project, a point object is used. This object has mass of m and the inclined plane makes an angle θ with the horizontal. This object is released from rest and slides down a frictional track of height h above the horizontal. At the bottom of the track, this object moves a long horizontal surface and hits a spring with force constant k at the end of this path. In all the path, this object is influenced by two kind of nonconservative force, namily the friction force and the wind-force. For the animation, the informations of of mass, coefficient of friction, a spring having a force constant k, other force (wind), the length of track inclined plane and horizontal is needed. The moving time, velocity, acceleration and energy kinetic are observed. The verification case is done using a simulation program with VB 6.0 to compare with the manual calculation. For another case, when us, uk1, uk2 and wind-force are set up to zero, the object will be harmonic motion.